2012
DOI: 10.1177/1756283x12450246
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab: a novel standard option for patients with HER-2-positive advanced gastric or gastro-oesophageal junction cancer

Abstract: Abstract:The human epidermal receptor-2 (HER-2) is amplified in up to 25% of patients with gastroesophageal adenocarcinomas. Although the presence of this amplification does not appear to confer a poor prognosis, it provides a valuable novel therapeutic target for this group of patients. Trastuzumab is a fully humanized monoclonal antibody directed at HER-2 which binds the external domain of the receptor and exerts its action via a combination of antibodydependent cytotoxicity, reduced shedding of the extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 96 publications
2
27
0
Order By: Relevance
“…Its superexpression is generally associated with tumors of epithelial origin, but with much varied frequency; studies focusing on gastric cancer or esophagogastric transition found rates varying from 5 to 25% [6, 9]. We found positivity in 3.3%, a little under the literature data.…”
Section: Discussionsupporting
confidence: 54%
“…Its superexpression is generally associated with tumors of epithelial origin, but with much varied frequency; studies focusing on gastric cancer or esophagogastric transition found rates varying from 5 to 25% [6, 9]. We found positivity in 3.3%, a little under the literature data.…”
Section: Discussionsupporting
confidence: 54%
“…Differences in HER2 dysregulation in primary solid tumors and metastases may, at least partially, explain HER2-targeted therapeutic inconsistencies. Trastuzumab has been approved for the treatment of advanced gastric cancer (GC) and GEJAC (69). While, HER2 is overexpressed in a number of cancers, the rate of HER2 amplification is variable in esophageal cancer (10) and few studies have investigated the different features of HER2 gene amplification among ESCC, GEJAC and GC.…”
Section: Introductionmentioning
confidence: 99%
“…This study and other similar studies suggest that ERBB2 is an important therapeutic target in these cases. It can be said that 15-25% of the cases with gastroesophageal cancers show ERBB2 expression similar to the breast cancers and about one in five cases with breast cancer is candidate for anti-ERBB2 treatment modalities [13]. Our case had proximal cancer and he lived about 2 years and brain metastasis developed.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand it has been shown that lapatinib reverses irinotecan resistance in vitro and it is reasonable to combine lapatinib and irinotecan which is an active drug in second line treatment of gastric cancer [17]. Another choice may be the combination of capecitabine, lapatinib and oxaliplatin which this regimen will be tested in LOGiC trial [13]. Trastuzumab and lapatinib combination which has been found to be effective in metastatic breast cancer may be another option [18].…”
Section: Discussionmentioning
confidence: 99%